THE ROLE OF GIFTS IN THE DIPLOMATIC TRADITIONS OF THE MONGOL EMPIRE AND THE GOLDEN HORDE (BASED ON THE WORKS OF WESTERN SCIENTISTS) (Journal of history, 2025)
The Mongol Empire and the Golden Horde left an important mark on the medieval history of Central Eurasia. A distinctive feature of the Mongol uluses after Islamization was the frequent appearance of Islamic items in their sent and received diplomatic parcels. The purpose of the study is to examine how Islamic gift objects and gift-giving practices reflected the new ideology, how they were received and understood by both sides in a particular context, and the extent to which they continued or deviated from the pre-Islamic Mongol tradition.The article used the works of Western scientists who touched upon in their research the diplomacy of Central Eurasia, diplomatic negotiations, the exchange of diplomatic gifts, including gifts of Islamic themes and their symbolic meanings, as well as the Mongolian protocol for receiving ambassadors and their rituals. Diplomatic gifts not only work as symbols that demonstrate sincerity for conducting formal diplomatic dialogues, the exchange of gifts is a matter of building trust. The authenticity and final results of these negotiations through correspondence must largely be confirmed through diplomatic gifts, treaties and rituals. Moreover, gift giving is part of symbolic competitions that demonstrate the status, power and generosity of the sender towards the recipient. The exchange of gifts was an integral component of diplomatic practice, and the ritual of gift-giving was a key element. In accordance with diplomatic protocol, ambassadors were regularly presented with gifts at welcoming receptions. Gifts primarily had a symbolic meaning; in some cases, rare and exclusive items were given. The goal was to ensure the continuation of friendly relations between the two countries. The importance of gift exchange rituals can be inferred from reports of gift refusal. This clearly meant that no agreement had been signed between the parties.
Keywords: collectivization, refugeehood, forced migration, otkochevka, re-evacuation, reverse migration.